Karakteristik sisik ikan nila merah sebagai bahan baku kolagen : Characteristics of red tilapia fish scales as raw materials for the collagen industry - Pertiwi, Rizsa Mustika; Nurilmala, Mala; Nurjanah, Nurjanah; Nurhayati, Tati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Fishery by-products can be used in the industry, for example, tilapia fish products, namely scales, bones, and heads, as a source of raw material for the collagen industry. This study aimed to determine the characteristics of red tilapia scales as raw materials for collagen. The fish scales were sun-dried for 2 days, and the dried scales were characterized and used to extract collagen. The analysis included yield calculations, proximate analysis, heavy metals, and amino acids from red tilapia fish scales. Red tilapia scales around 3.73±0.01%, head 24.91±0.03%, gills 4.32±0.01%, bones 19.19±0.02%, meat and skin 33.00±0.04% and viscera 14.85±0.01%. The chemical composition of red tilapia fish scales was 14.35 ± 0.09% water, 36.51±0.47% ash, 0.02±0.02% fat, 47.69±0.37% carbohydrate, 1.46±0.01% protein, and 196.52 kcal/100 g total energy content. Red tilapia scales also contain glycine (101,488.45±305.71 mg/g), proline (60,531.03±170.96 mg/g), and alanine (41,427.985±111.66 mg/g) as markers of collagen. Heavy metals such as arsenic, cadmium, and mercury were not detected, and lead was detected at 0.24 mg/kg. The characteristics of tilapia fish still contain components that can be used as raw materials in the collagen industry. The yield of collagen red tilapia was 14.70±3.25%. In the future, it is hoped that this product can be processed and further developed into raw materials for other industries to create a green industry.